2018
DOI: 10.25105/jmpj.v10i2.2277
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Modifikasi Technology Acceptance Model (Tam) Dalam E-Business

Abstract: <p><em>This study analyzed SMEs batik entrepreneurs in Cirebon to apply e-business. The TAM3 theory is used to create an analytical model in understanding the desires of the entrepreneur. The desire to use technology is due to the perception of the level of ease of use. The easier the user perception, the higher the ability to see the usefulness of technology, and the easier the perception of usage, the higher desire to utilize technology.</em><em> </em><em>The analysis resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 0 publications
2
9
0
9
Order By: Relevance
“…Perceived ease of use and perceived usefulness influence behavioral intention by eliminating attitude toward using in 2000 when TAM 2 was launched [5]. TAM is still considered relevant in translating the readiness of users to utilize information technology.…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
See 2 more Smart Citations
“…Perceived ease of use and perceived usefulness influence behavioral intention by eliminating attitude toward using in 2000 when TAM 2 was launched [5]. TAM is still considered relevant in translating the readiness of users to utilize information technology.…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…Perceived usefulness is a person's belief in using technology-based information so that one's work is getting better. Perceived usefulness is the use of a structured system which results in an increase in the performance ability of an individual with a good level of trust [5].…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the research of a result which was conducted by Setiawan and Sulistiowati (2017), it can be concluded that Perceived Ease of Use (PEOU) has a significant effect on Behavior Intention to Use (BI) on the use of e-business by entrepreneurs in Cirebon. It is in line with the finding of a study which was conducted by Tobbin and Kuwornu (2011), that Perceived Ease of Use (PEOU) is the most important determinant of Behavior Intention to Use (BI) in using mobile money transfers in Ghana, India.…”
Section: Intervariable Relationshipmentioning
confidence: 99%
“…Penerapan Modifikasi Technology Acceptance Model Dalam E-Business, Universitas Swadaya Gunung Jati. Penelitian ini dipublikasikan oleh Adi Setiawan dan Lisa Harry Sulistiowati di tahun 2017 [10]. Fokus penelitian adalah bagaimana mengukur penerimaan masyarakat, khususnya pelaku UMKM dalam menggunakan e-commerce.…”
Section: Penelitian Terkaitunclassified